Recent advances in the diagnosis and management of tuberculous meningitis. - Mai, N; Thwaites, G (Lippincott, Williams & Wilkins, 2016)
Purpose Tuberculous meningitis is a devastating infection that is hard to diagnose and treat. We have reviewed tuberculous meningitis original research published within the last 18 months, selecting papers which we consider have most advanced knowledge. Recent findings We review advances in diagnostic methods, anti-tuberculosis chemotherapy, and the common complications of tuberculous meningitis. New commercial molecular diagnostic tests, such as GeneXpert MTB/RIF, have an important role in tuberculous meningitis diagnosis, but as with all other available tests they lack sensitivity and cannot rule out the disease. Recent trials and pharmacokinetic studies have advanced understanding of the best anti-tuberculosis drug regimens for tuberculous meningitis, although optimal doses and duration remain uncertain, especially for young children. Good outcomes depend upon the careful management of the common complications (brain infarcts, tuberculomas, hydrocephalus and hyponatraemia) and controlling intracranial pressure. New tools, such as point-of-care ultrasound, may assist in the management, especially in the assessment of intravascular volume and raised intracranial pressure. Summary Disability-free survival from tuberculous meningitis depends upon rapid diagnosis, starting anti-tuberculosis drugs before the onset of coma, and managing complications. Progress is slow and threatened by emerging drug resistant bacteria, but new drugs and diagnostic technologies offer hope to future patients.